Cholecystokinin-2 Receptor Targeting with Radiolabeled Peptides: Current Status and Future Directions - Klingler, Maximilian; Hnn, Anton A.; Guggenberg, Elisabeth Von (Current Medicinal Chemistry, 2020)
A wide variety of radiolabeled peptide analogs for specific targeting of cholecystokinin- 2 receptors (CCK2R) has been developed in the last decades. Peptide probes based on the natural ligands Minigastrin (MG) and Cholecystokinin (CCK) have a high potential for molecular imaging and targeted radiotherapy of different human tumors, such as Medullary Thyroid Carcinoma (MTC) and Small Cell Lung Cancer (SCLC). MG analogs with high persistent uptake in CCK2R expressing tumors have been preferably used for the development of radiolabeled peptide analogs. The clinical translation of CCK2R targeting has been prevented due to high kidney uptake or low metabolic stability of the different radiopeptides developed. Great efforts in radiopharmaceutical development have been undertaken to overcome these limitations. Various modifications in the linear peptide sequence of MG have been introduced mainly with the aim to reduce kidney retention. Furthermore, improved tumor uptake could be obtained by in situ stabilization of the radiopeptide against enzymatic degradation through coinjection of peptidase inhibitors. Recent developments focusing on the stabilization of the Cterminal receptor binding sequence (Trp-Met-Asp-Phe-NH2) have led to new radiolabeled MG analogs with highly improved tumor uptake and tumor-to-kidney ratio. In this review, all the different aspects in the radiopharmaceutical development of CCK2R targeting peptide probes are covered, giving also an overview on the clinical investigations performed so far. The recent development of radiolabeled MG analogs, which are highly stabilized against enzymatic degradation in vivo, promises to have a high impact on the clinical management of patients with CCK2R expressing tumors in the near future.
Keywords: molecular imaging